AC Conductivity and Impedance Properties of 0.65Pb(Mg1/3Nb2/3)O-3-0.35PbTiO(3) Ceramics - Behera, Banarji [UNESP]; Araujo, E. B. [UNESP]; Reis, R. N. [UNESP]; Guerra, J. D. S. (Hindawi Publishing Corporation, 2009)
The electrical properties of 0.65Pb(Mg1/3Nb2/3)O-3-0.35(PbTiO3) ceramics over a wide range of frequencies (10(2)-10(6) Hz) and temperatures (30-225 degrees C) were studied using impedance spectroscopy technique. The impedance and electric permittivity were strongly temperature and frequency dependent. The activation energy, calculated from the temperature dependence of AC conductivity of the ceramics was found to be similar to 0.5 eV. The relaxation process in the ceramics was found to be of non-Debye type. The nature of Cole-Cole diagram reveals the contribution of grain (bulk) and grain boundary permittivity in the ceramics. Copyright (C) 2009 Banarji Behera et al.